2006
DOI: 10.1002/eat.20348
|View full text |Cite
|
Sign up to set email alerts
|

Disordered eating related behaviors among Arab schoolgirls in Israel: An epidemiological study

Abstract: Objective: To examine the prevalence of disordered eating attitudes and behaviors among three religious subgroups of Arab schoolgirls in Israel (Moslems, Druze, and Christians).Method: The sample consisted of 1,131 Arab schoolgirls in Israel, including 922 (81.5%) Moslem, 125 (11.1%) Christian, and 84 (7.4%) Druze adolescents, in the 7-12th grades. The sample was drawn from urban and rural residential settings from all parts of Israel using a clusters sampling method.Results: The Christian subgroup had a signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 39 publications
2
30
0
4
Order By: Relevance
“…Four studies have examined disordered eating attitudes and behaviours among Israeli-Arab adolescent girls in communal samples. The results revealed similar maladaptive eating behaviours among Arab adolescent females and their Jewish peers (Apter et al, 1994;Latzer, Tzischinsky, & Azaiza, 2007;Latzer, Tzischinsky, & Geraisy, 2007).…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…Four studies have examined disordered eating attitudes and behaviours among Israeli-Arab adolescent girls in communal samples. The results revealed similar maladaptive eating behaviours among Arab adolescent females and their Jewish peers (Apter et al, 1994;Latzer, Tzischinsky, & Azaiza, 2007;Latzer, Tzischinsky, & Geraisy, 2007).…”
Section: Introductionmentioning
confidence: 67%
“…They may also be related to the level of exposure to a westernised environment and the phenomenon of culture clash with western values (Soh, Touyz, & Surgenor, 2006). This tendency extends to Israel, a multicultural western country with various ethnic and religious groups, including Arab Muslims and Christians (Latzer, Tzischinsky, & Azaiza, 2007;Latzer, Tzischinsky, & Geraisy, 2007). Indeed, the prevalence of body dissatisfaction among Israeli-Arab adolescent girls was found to be 13% (Latzer, Tzischinsky, & Azaiza, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Previous researches have indicated that compared to Western women, Asian women experience less body dissatisfaction, and a larger body size was considered attractive 30 . Other studies in other places have focused on this, finding rates of body dissatisfaction at 16% in Saudi Arabia 31 , 13% in Palestine 32 , and approximately 12% in Pakistan 33 . Although these researches focused on adolescents, it must be considered that body image dissatisfaction can continue in adulthood 34 .…”
Section: Discussionmentioning
confidence: 92%
“…Os principais termos usados para caracterizar a presença de comportamentos de risco para TA foram "risco de transtornos alimentares" 13,[27][28][29][30]34,38,52,60,67,[77][78][79]81,82,88 e "comer transtornado" 35,39,41,[43][44][45][46]48,63,65,68,73,84,86 . Mesmo assim, mais de 60% dos estudos utilizaram outras diversas nomenclaturas e, no contexto do Brasil, observa-se que também não há padronização dos termos.…”
Section: Discussionunclassified